2020
DOI: 10.1159/000508691
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Psammomatoid Ossifying Fibroma of the Orbital Roof: A Rare Cause of Proptosis among Children

Abstract: • Juvenile psammomatoid ossifying fibroma (JPOF) is a rare bone tumor characterized by a predilection for the sinonasal region. • It usually presents as a punched-out lesion with sharp borders. It may have an aggressive course with a high local recurrence rate. Novel Insights • JPOF may rarely involve the orbital roof and cause proptosis in a child. It should be suspected as a rare cause of persistent/progressive proptosis in childhood. • The radiological appearance of a ground glass mass, which is typical of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Rahmani et al . reported that only 70 cases of JPOF were registered during the last 36 years [ 4 ]. These lesions display male predilection and usually develop during the first and the second decade of life [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rahmani et al . reported that only 70 cases of JPOF were registered during the last 36 years [ 4 ]. These lesions display male predilection and usually develop during the first and the second decade of life [ 5 ].…”
Section: Discussionmentioning
confidence: 99%